-8-9=-3(d+3)-5

Simple and best practice solution for -8-9=-3(d+3)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-9=-3(d+3)-5 equation:



-8-9=-3(d+3)-5
We move all terms to the left:
-8-9-(-3(d+3)-5)=0
We add all the numbers together, and all the variables
-(-3(d+3)-5)-17=0
We calculate terms in parentheses: -(-3(d+3)-5), so:
-3(d+3)-5
We multiply parentheses
-3d-9-5
We add all the numbers together, and all the variables
-3d-14
Back to the equation:
-(-3d-14)
We get rid of parentheses
3d+14-17=0
We add all the numbers together, and all the variables
3d-3=0
We move all terms containing d to the left, all other terms to the right
3d=3
d=3/3
d=1

See similar equations:

| 26×20=29x | | -2-j=-j-6 | | 2(2x+1)=5x-9 | | -20j-2=-3j-2-17j | | 40*x=20 | | 15=21-3k | | X2+10x+25=16 | | 16t-5-12t=31 | | 3-a=4a+122 | | 3.65+e=-10.75 | | 11-20r=-19r-5 | | x/x=1=4 | | 3=j/2-7 | | 6t-4=-6+6t | | |4t-5|=2t+1 | | 5=21-4p | | 2x+80=x+25 | | X+x+x+2x-9+2x-9=360 | | 2+7h-19=16+7h | | 3y-2(y-5)+3=7 | | 24=(v-92) | | 1+6t=79 | | X2+8x+16=1 | | 5f+5=55 | | Y=-2x+247 | | (x^2-5x+2)+(x^2+4x+5)-(x^2-6x-42=) | | 31.5=0.1x+0.18x | | 4(3-n)=8 | | 12x-11x=14 | | X+69+x+121=180 | | z/4+8=14 | | 4x+5=27-18 |

Equations solver categories